2018
DOI: 10.1038/nrdp.2017.107
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis

Abstract: Burkholderia pseudomallei is a Gram-negative environmental bacterium and the aetiological agent of melioidosis, a life-threatening infection that is estimated to account for ∼89,000 deaths per year worldwide. Diabetes mellitus is a major risk factor for melioidosis, and the global diabetes pandemic could increase the number of fatalities caused by melioidosis. Melioidosis is endemic across tropical areas, especially in southeast Asia and northern Australia. Disease manifestations can range from acute septicaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
792
0
37

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 505 publications
(910 citation statements)
references
References 260 publications
9
792
0
37
Order By: Relevance
“…B . pseudomallei is intrinsically resistant to most antibiotics, but a handful of antibiotics are effective for which emergence of newly resistant strains is rare (Sarovich et al, ; Schweizer, ; Wiersinga et al, ; Wuthiekanun et al, ). Still, therapeutic eradication of B .…”
Section: Introductionmentioning
confidence: 99%
“…B . pseudomallei is intrinsically resistant to most antibiotics, but a handful of antibiotics are effective for which emergence of newly resistant strains is rare (Sarovich et al, ; Schweizer, ; Wiersinga et al, ; Wuthiekanun et al, ). Still, therapeutic eradication of B .…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards clinical scores began to increase to a mean of 3·2 by day 30 pc, weight loss (4%) was also seen. This pattern of symptoms mimicks human subacute/chronic infection; in humans, chronic melioidosis is characterized as a symptomatic infection that lasts >2 months; the nonspecific signs and symptoms, during the incubation period, can often hinder the diagnosis and treatment of this disease (Wiersinga et al ). In this study, on day 10 pc, hepatic abscesses were present and hepatic degeneration and inflammation was observed, which is consistent with subacute/chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, melioidosis was considered to be geographically restricted to countries in southeast Asia and northern Australia, because these regions have reported the highest incidence and prevalence of the disease, where annual incidence is up to 50 cases per 100 000 people [1,2]; however, the incidence of melioidosis increases in diabetic patients and, for example, in northern Australia it is estimated to be 260 cases per 100 000 [13]. The appearance of sporadic melioidosis cases and further investigation to identify other endemic areas worldwide has now expanded the global map of the disease to cover more countries within tropical areas [14], including the western hemisphere (Africa and America) [15] and the majority of the Asian continent ( Fig.…”
Section: Predicted and Evidenced Global Incidence Of Diseasementioning
confidence: 99%
“…Further, the study also confirmed that B. pseudomallei isolates from African origin were transmitted to Central and South America between 1650 and 1850, which correspond to the period representing the slave trade. However, major roadblocks exist that prevent the effective determination of the burden of melioidosis, and those include diversity in the clinical manifestations, lack of basic microbiological facilities in several endemic areas, the lack of conventional bacterial identification methods and awareness and knowledge among health-care professionals and poor disease surveillance systems [2,16]. Recent efforts to educate health professionals in countries where melioidosis has been reported [18] is expected to result in a steady increase in the awareness and better diagnosis and identification of the pathogen.…”
Section: Predicted and Evidenced Global Incidence Of Diseasementioning
confidence: 99%
See 1 more Smart Citation